Adherence to the Mediterranean Diet Among Nutrition and Dietetics Students - madencioğlu, servet; Yücecan, Sevinç (Progress in Nutrition, 2022)
Objective: This study aimed to determine adherence to the Mediterranean diet among Nutrition and Dietetics students. Methods: A cross sectional survey was conducted with the voluntary participation of students. 127 nutrition and dietetic students studying at Near East University. The thematic analysis had used to conduct the data by the SPSS version 18.0. ‘‘Mediterranean diet score-MDS’’ was used to determine to the adherence to Mediterranean diet. 3-day food record and 45-item food frequency questionnaire were used. In addition, the survey questioned dietary habits, lifestyle habits and anthropometric measurements. Results: Adherence to Mediterranean diet was poor in 31% and moderate in 69% of the students. Adherence of the students to Mediterranean diet decreased towards their final year at the university (p= 0.001). Most of the students were minimal active. Male students were found more active than females (p=0.011). Female students had higher fat percentage (p=0.000), while males had higher waist circumstance (p=0.000). Female students were found to have increased body fat percentage as they continued the education (p=0.015). There was not found any significant correlation between physical activity, anthropometric measurements and adherence to the Mediterranean Diet. In addition, students had higher bread (80.2%) and pasta (34.10%) consumption whereas lower vegetables (38.6%), fruits (34.6%) and fish (42.5%) consumption. Conclusion: The findings indicate that the eating and lifestyle habits of the students, even those studying nutrition, should be improved.